ANALISIS PENGARUH KUALITAS PRODUK TERHADAP KEPUASAN KONSUMEN PADA PADA BENTO JOK SAGERI JAYA SOFA DI NANIA KEC. BAGUALA AMBON - Andrie Christina Salhuteru; Marie Chrestien Tahalele (P3M Politeknik Negeri Ambon, 2022)
The Bento Jok Segeri Jaya Sofa business was founded in 1984 which is a hereditary business by Mr. Iwan's family until today. Because, he also opened manufacturing services by visiting directly to places that consumers need. The business he started has also reached out of town to rural areas and villages because many consumers need his sofa making services. And from that business can also help his family's economy. The purpose of this study was to determine and analyze the effect of service quality on customer satisfaction at Bento Jok Sageri Jaya Sofa. The analysis technique that will be used in this study is a simple linear regression analysis technique. The results found are that the product quality variable has a t-test value of 9.214 and a significance value of 0.000 <0.05. This shows that product quality has a positive effect on consumer satisfaction. This can be seen from the respondents' answers on consumer quality with a positive Likert scale, the majority of which answered 4 which means agree and 5 which means strongly agree. And the respondents' answers to consumer satisfaction with a positive Likert scale measure where the majority answered 4 which means agree and 5 which means strongly agree. This means that the better the quality of consumers Bento Jok Segeri Jaya Sofa Di Nania, Baguala Ambon District, the higher the level of consumer satisfaction. With good product quality, physical inspection of product feasibility, monitoring and evaluation can be carried out continuously so that there is no decrease in consumer satisfaction. Based on the results of research on the effect of product quality on consumer satisfaction at Bento Jok Segeri Jaya Sofa in Nania, Baguala Ambon District, the following conclusions can be drawn: Product quality variable (X) has a positive and significant effect on consumer satisfaction seen from the results of the t test value of 9.214 and a significance value of 0.000 <0.05. With good product quality, a physical examination of the feasibility of product quality, monitoring and evaluation can be carried out continuously so that there is no decrease in product quality.